New records of spider flies (Diptera: Acroceridae) in neotropical jumping spiders (Araneae: Salticidae) - Hagopián, Damián; Laborda, Álvaro (Entomological Communications, 2023)
Salticidae is the most diverse family within the order Araneae. Acroceridae are obligate parasites of spiders, since they need them to complete their development. The aim of this study is to report for the first time the presence of the species Ogcodes argentinensis Schlinger, 1960 (Diptera: Acroceridae: Ogcodinae) in a sub-adult individual of Jollas leucoproctus (Mello-Leitão, 1944) (Salticidae: Sitticini: Sitticina) and the genus Acrocera Meigen, 1803 (Diptera: Acroceridae) in a sub-adult of Titanattus sciosciae Rubio, Baigorria & Stolar, 2021 (Salticidae: Thiodinini). Both spiders were collected in two different localities from Maldonado department in Uruguay.